Evaluation of alternately combining HPV viral load and 16/18 genotyping in secondary screening algorithms - Luo, Hongxue; Du, Hui; Belinson, Jerome L.; Wu, Ruifang (PloS one, 2019)
Correlation with HPV viral load and worsening cervical lesions had been reported, but its potential for triage after primary HPV screening has not been adequately explored, especially when combined with HPV-16/18 genotyping. To evaluate combinations of human papillomavirus (HPV) viral load and genotyping for HPV-16/18 as secondary screening strategies. The Shenzhen Cervical Cancer Screening Trial Ⅱ (SHENCCAST Ⅱ) database was re-analyzed to explore new screening algorithms using the results of Hybrid Capture 2 (HC2), Mass Array Matrix-Assisted Laser Desorption/Ionization Time-of-Flight Mass spectrometry System (MALDI-TOF-MS) and the ThinPrep cytologic test (TCT) obtained by endocervical sampling. Compared with the recommended screening strategy of genotyping HPV-16/18 plus reflex to cytology, using viral load (10 RLU/CO as threshold) plus reflex to cytology resulted in less cytology but had a significantly higher sensitivity for cervical intraepithelial neoplasia 2+ (CIN2+)/CIN3+ without considerable changes in specificity and referral rates. Both of the strategy of using viral load ≥10 RLU/CO as cut-point for immediate colposcopy followed by triage genotyping HPV-16/18 for the other positive (≥1<10 RLU/CO) and the strategy of referring HPV-16/18 positives for immediate colposcopy followed by triage viral load (10 RLU/CO as threshold) for non-HPV-16/18 positives had comparable screening efficacy with algorithims that contain cytology. Primary HPV screening with triage of HPV-positive women by a combination of viral load and genotyping for HPV-16/18 provides good balance between sensitivity and specificity, the number of tests required, and referral rates.